Non-invasive detection of severe PH in lung disease using magnetic resonance imaging - Alkhanfar, Dheyaa; Dwivedi, Krit; Alandejani, Faisal; Shahin, Yousef; Alabed, Samer; Johns, Chris; Garg, Pankaj; Thompson, A. A. Roger; Rothman, Alexander M. K.; Hameed, Abdul; Charalampopoulos, Athanasios; Wild, Jim M.; et al. (Frontiers in Cardiovascular Medicine, 2023)
Abstract Introduction Severe pulmonary hypertension (mean pulmonary artery pressure ≥35mmHg) in chronic lung disease (PH-CLD) is associated with high mortality and morbidity. Data suggesting potential response to vasodilator therapy in patients with PH-CLD is emerging. The current diagnostic strategy utilises transthoracic Echocardiography (TTE), which can be technically challenging in some patients with advanced CLD. The aim of this study was to evaluate the diagnostic role of MRI models to diagnose severe PH in CLD. Methods 167 patients with CLD referred for suspected PH who underwent baseline cardiac MRI, pulmonary function tests and right heart catheterisation were identified. In a derivation cohort (n=67) a bi-logistic regression model was developed to identify severe PH and compared to a previously published multiparameter model (Whitfield model), which is based on interventricular septal angle, ventricular mass index and diastolic pulmonary artery area. The model was evaluated in a test cohort. Results The CLD-PH MRI model [= (-13.104) + (13.059 * VMI) - (0.237 * PA RAC) + (0.083 * Systolic Septal Angle)], had high accuracy in the test cohort (area under the ROC curve (0.91) (p<0.0001), sensitivity 92.3%, specificity 70.2%, PPV 77.4%, and NPV 89.2%. The Whitfield model also had high accuracy in the test cohort (area under the ROC curve (0.92) (p<0.0001), sensitivity 80.8%, specificity 87.2%, PPV 87.5%, and NPV 80.4%. Conclusion: The CLD-PH MRI model and Whitfield model have high accuracy to detect severe PH in CLD, and have strong prognostic value.